PERBEDAAN DOSIS ALUMINIUM SULFAT (TAWAS) TERHADAP KUALITAS SPERMATOZOA DAN KADAR ALUMINIUM DALAM TESTIS MENCIT (Mus Musculus) SWISS WEBSTER - Nuraini Hidayah Khasanah; Gratiana Ekaningsih Wijayanti; Sorta Basar Ida Simanjuntak (Scripta Biologica, 2018)
This study designated to evaluate the quality of reproductive organs system in the form of testicular weight, testicular volume and weight of epididymis; quality of spermatozoa include concentration, viability, motility, and morphology of spermatozoa; and aluminum accumulation in mice testis after administration of different aluminum sulfate dose, i.e., 0, 122,5, 245 and 490 mg/kg bb for 45 days were orally administrated using feeding tube through oral route for 45 days. The next objective is to evaluate the correlation between the doses of aluminum sulfate with each variable, as well as to assess the most influential doses of aluminum sulfate in reducing testicular weight and volume, epididymal weight, concentration, viability, motility, and morphology of cauda epididymal spermatozoa and increasing aluminum levels in testes Mice. The results showed that aluminum sulfate did not significantly (p>0.05) decrease testicular weight, testicular volume, epididymal weight, concentration and viability of spermatozoa, but significantly (p<0.05) decreased spermatozoa motility at doses of 245 and 490 mg/kg bb and reduce the proportion of spermatozoa with normal morphology at 490 mg/kg BW. The decrease of motility and percentage of spermatozoa with normal morphology is inversely proportional to the dose of aluminum sulfate each with the value of r = -0.034 and r = -457. Administration of aluminum sulfate for 45 days did not increase aluminum levels in the testes of mice. The use of aluminum sulfate in food processing or drinking water is still safe for human reproductive health.